Design, synthesis and properties of orthopalladated complexes: Proheterogeneous catalyst. (28th May 2016) - Das, Uttam; Pattanayak, Poulami; Patra, Debprasad; Brandão, Paula; Felix, Vitor; Chattopadhyay, Surajit
Graphical abstract: Two newly synthesized orthopalladated complexes were prepared and characterized unequivocally. Both the complexes contain a free uncoordinated phenolic –OH group. Both the complexes exhibited good catalytic efficacy toward C–C coupling reactions. It was found that compound2 was more appropriate for immobilization on a heterogeneous support. Abstract: The reaction of multidentate ligand, 3-((E)-(2-((E)-4-aryldiazenyl)phenylimino)methyl)benzene-1, 2-diol, H2 L (H2 L 1, 1a ; H2 L 2, 1b and H2 L 3, 1c ) and (E)-2-((2-(aryldiazenyl)phenylamino)methyl)phenol, HA (HA 1, 3a ; HA 2, 3b and HA 3, 3c ) [where H represents the dissociable protons upon complexation, and aryl groups of H2 L and HA are phenyl for H2 L 1 and HA 1, p -methylphenyl for H2 L 2 and HA 2, and p -chlorophenyl for H2 L 3 and HA 3 ], with Na2 PdCl4 separately afforded orthometallated complexes [(L)Pd], (2a, 2b and2c) and [(A)PdCl] (4a, 4b and4c) respectively. In the case of [(L)Pd], the deprotonated L 2− ligands bind palladium (II) in a tetradentate (C, N, N, O) fashion whereas in the case of [(A)PdCl], the deprotonated A − ligands bind Pd(II) in tridentate (C, N, N) manner. X-ray structures of [(L 1 )Pd], (2a) and [(A 1 )PdCl] (4a ) were determined to confirm the molecular structures. Both the complexes4a and5a exhibited catalytic activity toward Suzuki and Heck reactions. Conversion of [(A)PdCl] to its oxidized form upon ligand oxidation is reported.